Pembelajaran Matematika Realistik dengan Metode Penemuan Berbantuan Interactive Multimedia Ditinjau Dari Respon Belajar - Henry Suryo Bintoro (Universitas PGRI Madiun, 2017)
The purpose of this study was to determine: (1) whether the learning of mathematics realistic discovery methods aided interactive multimedia produce learning achievement better than conventional learning, (2) whether there is influence students' response to mathematics achievement, (3) whether there is an interaction between learning mathematics with students 'response to students' mathematics achievement. This study uses a quasi-experimental research methods. The population in this study were all fifth grade students of the second semester of the Holy Hadipolo village primary school year 2016/2017, while samples were selected by cluster random sampling is SD 3 Hadipolo as an experimental group with a total of 25 students and SD 2 Hadipolo as a control group by number 25 students. The results showed (1) there are differences in the effect of teaching methods to mathematics achievement, (2) there are differences in mathematics achievement among students with the response study of high, medium, and low., (3) there are differences in the achievement of each learning method consistent at each level of learning responses and differences in learning achievement of each level of learning consistent response to each method of learning.